Non-uniform Transmission Line Model of Offshore Wind Turbine Tower - Yuanjian SONG; Zheng XU; Jingqiu YU; Zheren ZHANG (Zhongguo dianli)
The modeling of wind turbine tower is an important part of the research on lightning protection of offshore wind turbines. The establishment of its model has an important impact on the analysis results. This paper first analyzes the inapplicability of the tower multi-surge impedance model in the research of lightning protection for offshore wind turbines, and then establishes a non-uniform transmission line model of tower. Secondly, the influence of the spatial structure change of the tower on its own electromagnetic transient characteristics was studied by using the multi-surge impedance model. The results show that the more the tower is divided into sections, the more accurate its electromagnetic transient response is. Finally, a comparative analysis of the lightning transient response of the tower using the non-uniform transmission line model and the multi-surge impedance model is performed, which proves that the non-uniform transmission line model is more in line with actual conditions.